2003
DOI: 10.1381/096089203765887697
|View full text |Cite
|
Sign up to set email alerts
|

Contraceptive Treatment after Biliopancreatic Diversion Needs Consensus

Abstract: Pregnancy should be avoided for 12 to 18 months after BPD. Fertility increases after BPD. As oral contraception is most popular and less reliable, we strongly believe that large multi-centre, prospective, randomized studies are necessary to come to a consensus about the use of contraceptive therapy after BPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0
9

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(73 citation statements)
references
References 12 publications
0
64
0
9
Order By: Relevance
“…Two reviews of patients undergoing bariatric surgery noted either resolution or improvement of type 2 diabetes mellitus. [38][39][40] Weight loss was also associated with a reduction in cholesterol and triglyceride levels as well as normalization of blood pressure and obstructive sleep apnea. 39 Given the improvements seen in both diabetes and hypertension, one can presume that similar resolution of hormonal milieu occurs with the reproductive hormones, thereby causing a return to fertility.…”
Section: Obesity Treatmentsmentioning
confidence: 98%
See 3 more Smart Citations
“…Two reviews of patients undergoing bariatric surgery noted either resolution or improvement of type 2 diabetes mellitus. [38][39][40] Weight loss was also associated with a reduction in cholesterol and triglyceride levels as well as normalization of blood pressure and obstructive sleep apnea. 39 Given the improvements seen in both diabetes and hypertension, one can presume that similar resolution of hormonal milieu occurs with the reproductive hormones, thereby causing a return to fertility.…”
Section: Obesity Treatmentsmentioning
confidence: 98%
“…It has been reported that approximately 10% of women aged ,40 years will become pregnant within 3 years of bariatric surgery. [38][39][40][41][42][43] The literature on pregnancy outcomes and complications in women who have undergone weight-loss surgery is limited and conflicting. 43 Generally, it is recommended that women defer pregnancy until at least 1 to 2 years postoperatively, corresponding to the period when the most rapid weight loss occurs.…”
Section: Obesity Treatmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the reproductive hormone profile and pregnancy outcomes, fertility status improves rapidly after bariatric surgery [51]. However, women who have undergone a bariatric procedure should be aware of possibly lower efficacy of contraceptives, due to malabsorption and post-operative complications, such as diarrhea and vomiting.…”
Section: Oral Contraceptivesmentioning
confidence: 99%